Evaluation of library service to rural physician associate program students. - Foreman, G E (1976)
Medical students participating in the Rural Physician Associate Program in Minnesota enjoy a unique educational experience, but local library resources are not adequate to support the program. To rectify this deficiency a library service program has been initiated, with the computer-based bibliography and photoduplication the principal service elements. Because of positive evaluation by the students, the service will be continued and expanded.